RETRACTED: Closed cycle economy is an effective model of country development - Tabaev Azamat; Talipova Dilfuza; Raimjanova Madina; Saidov Rasulbek; Askarova Mavluda (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001